Proceedings of the International Conference on Language, Literature, and Education (ICLLE 2018) 2018
DOI: 10.2991/iclle-18.2018.70
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical Cohesion In The Thesis

Abstract: The purpose of this study is (1) to explain the use of grammatical cohesion on the aspects of reference, substitution, ellipsis, and conjunction in the students' thesis; (2) explain the quality of thesis writing. The object of this research is thesis student of Faculty of Language and Arts Universitas Negeri Padang with number of research sample 15 thesis. Samples are taken randomly from thesis sets in 2015, 2016, and 2017. Data collection methods and techniques are language methods. The technique used is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Furthermore, the background and literature review section is meant to describe a review of literature that an author has investigated when studying a particular topic. The finding on a reference as the most dominant grammatical cohesion was also proved in research by (Puteri et al, 2018) from Universitas Negeri Padang, Indonesia, entitled grammatical cohesion in the thesis. The results showed that there were grammatical cohesion signals from dominant to least used in 192 paragraphs with 362 pairs of sentences: (1) references, (2) conjunction, (3) ellipsis, and (4) substitution.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, the background and literature review section is meant to describe a review of literature that an author has investigated when studying a particular topic. The finding on a reference as the most dominant grammatical cohesion was also proved in research by (Puteri et al, 2018) from Universitas Negeri Padang, Indonesia, entitled grammatical cohesion in the thesis. The results showed that there were grammatical cohesion signals from dominant to least used in 192 paragraphs with 362 pairs of sentences: (1) references, (2) conjunction, (3) ellipsis, and (4) substitution.…”
Section: Discussionsupporting
confidence: 58%
“…Cohesion in the headlines of student newspapers. However, the findings are not very significant because grammatical cohesion in student thesis tends to be appropriate for its use [7].…”
Section: Introductionmentioning
confidence: 81%
“…The researcher analyzed the pairs of sentences in each sample studied. Steps for analyzing data in detail, as follows: (1) coding each sentence containing aspects of grammatical cohesion; (2) classifying aspects of grammatical cohesion in each sample; (3) analyze grammatical cohesion in all aspects with sentence pairing techniques; (4) compiling into a supporting table all aspects of grammatical cohesion found; (5) concocting findings; (6) determine the quality of grammatical cohesion using the 10 scale conversion guidelines; (7) conclude the results of the study.…”
Section: Methodsmentioning
confidence: 99%